Comparative effects of dexmedetomidine, propofol, sevoflurane, and S-ketamine on regional cerebral glucose metabolism in humans: a positron emission tomography study - Laaksonen L.; Kallioinen M.; Långsjö J.; Laitio T.; Scheinin A.; Scheinin J.; Kaisti K.; Maksimow A.; Kallionpää R.E.; Rajala V.; Johansson J.; Kantonen O.; et al. (ELSEVIER SCI LTD, 2022)
Introduction: The highly selective alpha(2)-agonist dexmedetomidine has become a popular sedative for neurointensive care patients. However, earlier studies have raised concern that dexmedetomidine might reduce cerebral blood flow without a concomitant decrease in metabolism. Here, we compared the effects of dexmedetomidine on the regional cerebral metabolic rate of glucose (CMRglu) with three commonly used anaesthetic drugs at equi-sedative doses.
Methods: One hundred and sixty healthy male subjects were randomised to EC50 for verbal command of dexmedetomidine (1.5 ng ml (1); n=40), propofol (1.7 mu g ml (1); n=40), sevoflurane (0.9% end-tidal; n=40) or S-ketamine (0.75 mu g ml (1); n=20) or placebo (n=20). Anaesthetics were administered using target-controlled infusion or vapouriser with end-tidal monitoring. F-18-labelled fluorodeoxyglucose was administered 20 min after commencement of anaesthetic administration, and high-resolution positron emission tomography with arterial blood activity samples was used to quantify absolute CMRglu for whole brain and 15 brain regions.
Results: At the time of [F-18]fluorodeoxyglucose injection, 55% of dexmedetomidine, 45% of propofol, 85% of sevoflurane, 45% of S-ketamine, and 0% of placebo subjects were unresponsive. Whole brain CMRglu was 63%, 71%, 71%, and 96% of placebo in the dexmedetomidine, propofol, sevoflurane, and S-ketamine groups, respectively (P<0.001 between the groups). The lowest CMRglu was observed in nearly all brain regions with dexmedetomidine (P<0.05 compared with all other groups). With S-ketamine, CMRglu did not differ from placebo.
Conclusions: At equi-sedative doses in humans, potency in reducing CMRglu was dexmedetomidine>propofol>ketamine=placebo. These findings alleviate concerns for dexmedetomidine-induced vasoconstriction and cerebral ischaemia.